Produção e caracterização de micropartículas lipídicas contendo ferro produzidas por spray chilling - Silva, Yasmim Fernanda da (2022)
Micronutrient deficiency is a major global health problem, mainly caused by diets lacking in essential nutrients. Iron deficiency is considered the most prevalent nutritional disorder in the world. To combat the lack of micronutrients in one’s diet, food fortification strategies can be applied. However, direct fortification of foods with iron can result in undesirable sensory changes in the color, odor, and taste of foods. In this context, the use of encapsulation processes may help to avoid or to mask unwanted sensory changes in fortified foods and, at the same time, it may reduce the interaction of this element with food components, further increasing its bioavailability. Among the various techniques used for microencapsulation, the spray chilling technique, also known as spray cooling or spray congealing, has been receiving special attention due to its advantages over other techniques, including the use of low temperatures. Therefore, the objective of this work was to produce microparticles containing iron, encapsulated in a lipid matrix, using the spray chilling technique, and to evaluate its properties and the characteristics of iron release. Formulations with different proportions of beeswax and cocoa butter were evaluated. Lipid microparticles obtained by spray chilling were evaluated by X-ray diffraction, particle size, yield, retention efficiency and surface morphology. The effect of different temperatures (10, 20, 30 and 40 oC) on the iron release profile present in the microparticles was evaluated. Release kinetics was evaluated using zero-order, first-order, Korsmeyer-Peppas and Higuchi models. Iron release in a simulated gastrointestinal system was also studied. The microparticles obtained short spacing values which indicate a β' polymorphic characteristic. The mean diameters of the lipid microparticles ranged from 25.9 to 31.4 μm. The process yield reached values of up to 75.0%. The efficiency of the microencapsulation obtained was, on average, 75.2%. Scanning electron microscopy analysis showed that the surfaces of the microparticles containing cocoa butter had shapes which were irregular, agglomerated, and varied in size. The lowest iron release was observed in treatment 4, consisting of beeswax and cocoa butter in a proportion of 1:1 m/m. The presence of cocoa butter reduced the intensity of iron release by the lipid microparticles. The release mechanism observed in the release kinetics was diffusion and relaxation, and the model that best fitted the data obtained was the zero-order model. The results showed that the lipid matrix was able to protect and prevent the release in the simulated gastric medium, allowing a more significant release in the simulated intestinal medium with percentages from 36.1% to 56.3%. The microparticles loaded with ferrous sulfate produced by spray chilling proved to be a promising system for carrying iron with potential application in foods.